Historical and future black carbon deposition on the three ice caps: Ice core measurements and model simulations from 1850 to 2100. Issue 14 (29th July 2013) - Bauer, Susanne E.; Bausch, Alexandra; Nazarenko, Larissa; Tsigaridis, Kostas; Xu, Baiqing; Edwards, Ross; Bisiaux, Marion; McConnell, Joe
Abstract: [1] Ice core measurements in conjunction with climate model simulations are of tremendous value when examining anthropogenic and natural aerosol loads and their role in past and future climates. Refractory black carbon (BC) records from the Arctic, the Antarctic, and the Himalayas are analyzed using three transient climate simulations performed with the Goddard Institute for Space Studies ModelE. Simulations differ in aerosol schemes (bulk aerosols vs. aerosol microphysics) and ocean couplings (fully coupled vs. prescribed ocean). Regional analyses for past (1850–2005) and future (2005–2100) carbonaceous aerosol simulations focus on the Antarctic, Greenland, and the Himalayas. Measurements from locations in the Antarctic show clean conditions with no detectable trend over the past 150 years. Historical atmospheric deposition of BC and sulfur in Greenland shows strong trends and is primarily influenced by emissions from early twentieth century agricultural and domestic practices. Models fail to reproduce observations of a sharp eightfold BC increase in Greenland at the beginning of the twentieth century that could be due to the only threefold increase in the North American emission inventory. BC deposition in Greenland is about 10 times greater than in Antarctica and 10 times less than in Tibet. The Himalayas show the most complicated transport patterns, due to the complex terrain and dynamical regimes of this region. Projections of future climate based on the four CMIP5 Representative Concentration Pathways indicate further dramatic advances of pollution to the Tibetan Plateau along with decreasing BC deposition fluxes in Greenland and the Antarctic. Key Points: BC residence times of about 4 days seems realistic Models fail to reproduce the sharp 8‐fold observed BC increase Further dramatic increase of pollution reaching the Tibetan plateau predicted